Reducing Catheter-associated Urinary Tract Infections via Cost-saving Diagnostic Stewardship. (6th October 2020) - Luu, Allison; Dominguez, Fernando; Yeshoua, Brandon; Vo, Christopher; Nallapa, Swathi; Chung, David; Wald-Dickler, Noah; Butler-Wu, Susan M; Khaleel, Huda; Chang, Kate; Canamar, Catherine P; Holtom, Paul; et al.
Abstract: We conducted a quality improvement project at our large, public, tertiary-care, academic hospital to reduce the standardized infection ratio (SIR) of hospital-acquired catheter-associated urinary tract infections (CAUTIs). Our diagnostic stewardship program, based on education and audit and feedback, significantly reduced inpatient urine culture orders and CAUTI SIR.